2015
DOI: 10.1037/bul0000004
|View full text |Cite
|
Sign up to set email alerts
|

Global processing takes time: A meta-analysis on local–global visual processing in ASD.

Abstract: What does an individual with autism spectrum disorder (ASD) perceive first: the forest or the trees? In spite of 30 years of research and influential theories like the weak central coherence (WCC) theory and the enhanced perceptual functioning (EPF) account, the interplay of local and global visual processing in ASD remains only partly understood. Research findings vary in indicating a local processing bias or a global processing deficit, and often contradict each other. We have applied a formal meta-analytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
237
2
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(271 citation statements)
references
References 99 publications
27
237
2
5
Order By: Relevance
“…The papers in this special section by Booth and Happé (2017), together with a recent publication elsewhere in this journal by Guy et al (2017) are sympathetic to what is now called "weak coherence" (Happé and Frith 2006) and the EPF accounts respectively and give up-to-date interpretations of them in the light of more recent findings, particularly as viewed through the lens of the Van der Hallen et al (2015) meta-analysis. Interestingly, both studies confirm the finding of Van der Hallen et al (2015) that the most robust difference between ASD and TD populations in this context is local-to-global interference in the temporal component of visual processing, although, in typical fashion for the field, a more-recent study by Van der Hallen et al (2017b) has not confirmed this result in a larger group. Van Eylen et al (2017) provide a theoretically agnostic comparison of local versus global processing abilities in ASD and TD individuals using a battery of tests on a large, well-characterized group.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…The papers in this special section by Booth and Happé (2017), together with a recent publication elsewhere in this journal by Guy et al (2017) are sympathetic to what is now called "weak coherence" (Happé and Frith 2006) and the EPF accounts respectively and give up-to-date interpretations of them in the light of more recent findings, particularly as viewed through the lens of the Van der Hallen et al (2015) meta-analysis. Interestingly, both studies confirm the finding of Van der Hallen et al (2015) that the most robust difference between ASD and TD populations in this context is local-to-global interference in the temporal component of visual processing, although, in typical fashion for the field, a more-recent study by Van der Hallen et al (2017b) has not confirmed this result in a larger group. Van Eylen et al (2017) provide a theoretically agnostic comparison of local versus global processing abilities in ASD and TD individuals using a battery of tests on a large, well-characterized group.…”
supporting
confidence: 51%
“…general review of the literature on vision in Autism Spectrum Disorder (Simmons et al 2009) and the more recent publication, from the Leuven group of which Dr. Boets was then a part, of a meta-analysis focused on the topic (van der Hallen et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, including that single discrete variable as a moderator in the syntax (i.e., after the mods~element) would suffice. However, it has become rather common to report on the mean effect (as well as significance and confidence interval) of all categories of a discrete potential moderating variable (see, for instance, Assink et al, 2015;Houben et al, 2015;Rapp, Van den Noortgate, Broekaert, & Vanderplasschen, 2014;Van der Hallen, Evers, Brewaeys, Van den Noortgate, & Wagemans, 2015;Van der Stouwe, Asscher, Stams, Dekovic, & Van der Laan, 2014;Weisz et al, 2013 # Determine the potential moderating effect of publication status; # Unpublished studies are now tested against published # studies, so published studies serve as the reference category; # Print the results stored in the object "published" on screen. published <-rma.mv(y, v, mods =~pstatnotpub, random = list(~1 | effectsizeID,1 | studyID), tdist=TRUE, data=dataset) summary(published, digits=3)…”
Section: Categorical Moderators With Three Categoriesmentioning
confidence: 99%
“…Global processing is not impossible for most individuals with ASC, but is more difficult and demands effort (Koldewyn et al, 2013;Stevenson et al, 2016). A meta-analysis of visuo-spatial performance tests in autism spectrum disorders shows superior performance in both embedded figures testing and block design and another meta-analysis suggests slower global processing in ASD ( Van der Hallen et al, 2015). It is suggested that these differences are related to differences in brain connectivity (Belmonte et al, 2004) and that they profoundly affect how different individuals interact with their material and social worlds.…”
Section: The Relationship Between Local Processing Bias and Autismmentioning
confidence: 99%